Evaluation of Planning and Strategic Management at Social Organization for Business Sustainability - Azmy, Ahmad; Hutabarat, Reynold Bachtiar (Jurnal Economia, 2024)
AbstractThis research analyzes the evaluation of programs and strategic management planning of social organizations. A qualitative approach is used as part of photographing the state and potential of the organization for the greatest achievement as an educational organization with the best reputation. The process of collecting data by interview. The results showed that the Good to Great theoretical framework can be used as a tool for measuring or evaluating programs and strategic management of organizations by identifying various strengths and weaknesses that become spaces for organizational improvement, based on each characteristic of the principles studied. Research proves that the Discipline of People, Discipline of Ideas, and Discipline of Action in the framework of Good to Great theory can be applied and relevant as an evaluation framework in the context of a social organization in Indonesia. These three aspects show a sustainable business with superior programs according to organizational values. Keywords:Business Sustainability, Business Planning, Strategic Management, Social Organization